Kegiatan Ekstrakulikuler Sebagai Media Penguatan Moderasi Beragama Di SMA Negeri 4 Palangka Raya - Vedhic Igrey Hakavolta; Hamdanah Hamdanah; Saiful Lutfi (Mathematics Education Study Program, 2025)
Religious moderation is an essential aspect of fostering harmony and tolerance in a pluralistic society, especially in a school environment composed of diverse religious and cultural backgrounds. Extracurricular activities not only strengthen social bonds among students but also instill values of moderation that support the creation of an inclusive and tolerant educational environment. Schools can maximize the potential of extracurricular activities as a medium for strengthening religious moderation, which in turn will support educational efforts to shape a generation with a moderate outlook on religion. The aims of this study are to identify (1) the role of strengthening religious moderation at SMAN 4 Palangka Raya, and (2) the implementation of the Pencak Silat extracurricular activities at SMAN 4 Palangka Raya. This study employs a qualitative research method presented descriptively. Data collection techniques include observation, interviews, and documentation, while data validation techniques utilize source triangulation and technique triangulation. Data analysis techniques involve data collection, data reduction, data presentation, and conclusion drawing. The results are (1) the role of strengthening religious moderation at SMAN 4 Palangka Raya, and (2) the implementation of Pencak Silat extracurricular activities at SMAN 4 Palangka Raya.